Ranging via ultra wideband (UWB) radio - Ong, Lee Shan (2014)
Ultra- Wideband (UWB) Radios is an electromagnetic waveform formed by a sequence of very short pulses. It has large bandwidth with low energy level. Ultrasound is a sound wave with the frequency from 20kHz to several GHz. In this experiment, both UWB and ultrasound is used for ranging purpose and then the result obtained is compared to examine their performance. For UWB, 3 different techniques are used which are peak detection, conventional correlator and asymmetric phase only correlator (APOC). The result is used to compare with the one obtained from ultrasound. Finally, the correlation coefficient for all the techniques together with ultrasound is computed. The higher the speeds of the moving object, the lower the correlation coefficient with less accuracy. For experiments which are carried out indoors, ultrasound and UWB both have high correlation coefficient. However, UWB will have better performance for outdoors because it is not affected by surrounding temperature and humidity which affects ultrasound.